Effectiveness of Chewing Gum Containing CPP-ACP for Remineralisation of Demineralised Enamel around Orthodontic Brackets: An in Situ Study - Matheus Melo Pithon; Amir Felipe Souza dos Santos; Adrielle Mangabeira dos Santos; Tatiana Kelly da Silva Fidalgo; Adilis Kalina Alexandria de França; Raildo Silva Coqueiro; Ana Carolina Dias Viana de Andrade; Dauro Douglas Oliveira; Lucianne Cople Maia (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the effectiveness of chewing gums containing CPP-ACP in remineralisation of demineralised enamel around orthodontic brackets. Material and Methods: Enamel blocks from 120 bovine incisors were used. The blocks were flattened and polished, followed by the development of incipient subsurface caries. The blocks have been subjected to a baseline microhardness analysis. Orthodontic brackets were bonded to the exposed area of the blocks, reserving an area for hardness analysis. An in situ crossover (three-way crossover phases of 21 days with an interval of one week between them), controlled, randomised and blind experimental model was used, with the participation of 12 volunteers divided into groups: G1 - negative control group, without chewing gum; G2 - conventional sugar-free chewing gum, without CPP-ACP (placebo); and G3 - sugar-free chewing gum with CPP-ACP. The following parameters were analysed: superficial linear (Ra), volumetric roughness (Sa), and superficial structural loss, which was indicated by Gap measurement (difference between the healthy and treated area). Statistical tests used were the Friedman, Wilcoxon and Shapiro-Wilk, Kruskal Wallis' nonparametric tests and ANOVA. Results: There was a significant reduction in enamel microhardness after demineralisation in all the groups (p<0.05). This deleterious effect was attenuated in the three groups after the final evaluation, although there were no statistical differences (p<0.05); however, the final values did not return to the baseline values (p<0.05). Conclusion: Chewing gum containing CPP-ACP did not promote in situ remineralisation of demineralised enamel around orthodontic brackets.